2006
DOI: 10.1109/ted.2006.871870
|View full text |Cite
|
Sign up to set email alerts
|

Merits of heat assist for melt laser annealing

Abstract: In this paper, the potential for sub-10-nm junction formation of partial-melt laser annealing (PMLA), which is a combination of solid-phase regrowth and heat-assisted laser annealing (HALA), is demonstrated. HALA and PMLA are effective for reducing laser-energy density for dopant activation and for improving heating uniformity of device structure. The absence of melting at the dopant profile tail for PMLA results in a negligibly small diffusion at this region. A high activation rate is achievable by melting th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…There are recent studies that indicate that these technologies could be equivalent to current technologies from a transistor stand-point (7). While one technique capitalizes on solid-phase epitaxy (microwave annealing), the other one relies on the highest form of non-equilibrium or metastable heating in order to freeze the dopants in the lattice (melt annealing) (9,10,11).…”
Section: Introductionmentioning
confidence: 99%
“…There are recent studies that indicate that these technologies could be equivalent to current technologies from a transistor stand-point (7). While one technique capitalizes on solid-phase epitaxy (microwave annealing), the other one relies on the highest form of non-equilibrium or metastable heating in order to freeze the dopants in the lattice (melt annealing) (9,10,11).…”
Section: Introductionmentioning
confidence: 99%
“…Arsenic is the most widely used silicon dopant for n-type layers in this context. 7,8 Here, we investigate the diffusion and segregation of ultrashallow Sb implants. 1 and 2͒.…”
Section: Introductionmentioning
confidence: 99%
“…Solid Phase Epitaxial Regrowth (SPER) has been shown to achieve supersaturation higher than the normal Si solubility limit for some dopants. A further increase in activation above SPER can be achieved by Liquid Phase Epitaxial Regrowth (LPER), using a pulsed laser for 10~100 ns [24,25,26] to locally melt the amorphized area. This laser melt anneal enables a box-like dopant profile at far beyond the equilibrium activation level.…”
Section: Supersaturationmentioning
confidence: 99%
“…This laser melt anneal enables a box-like dopant profile at far beyond the equilibrium activation level. [25] Recent studies, however, showed that melt process and dopant activation levels achievable with LPER can be highly variable due to the very short anneal and high cool-down quenching rates, [27] indicating that a significant optimization effort may be needed to use this technique.…”
Section: Supersaturationmentioning
confidence: 99%